A systematic review of outpatient billing practices. (May 2022) - Burks, Kristie; Shields, Jessie; Evans, Joseph; Plumley, Jodi; Gerlach, Jarrett; Flesher, Susan
Objectives: Healthcare coding and billing are an important aspect of practice management that directly impacts the financial stability of a health care practice. To financially sustain or grow a medical practice, it is imperative that resident and faculty physicians have knowledge and skills for accurate billing in every patient encounter. Methods: A systematic review was conducted to identify recently published studies that report on improvements in medical coding and billing accuracy, clinical documentation, and reimbursement rate. A search of three databases yielded a total of 5754 records. After screening, 41 records were sought for retrieval and a total of 18 records were obtained for review. Results: Following a thorough review of literature, the most common reasons for inaccurate or inappropriate billing were a lack of formal education within residency curriculum, inadequate clinical documentation supporting level of billing, and lack of a feedback system aimed to correct billing errors. Conclusion: A formal education curriculum implemented in training could enhance knowledge and application of accurate billing and coding and further benefit practice longevity. The purpose of this systematic review is to apply knowledge gained to the development and implementation of a quality improvement study intended to improve accuracy of coding and billing within an academic pediatric outpatient center.